Fairhaven rising - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce, 2021)
"Sixteen years have passed since the mage Beltur helped to found the town of Fairhaven, and Taelya, Beltur's adopted niece, is now a white mage undercaptain in the Road Guards of Fairhaven. Fairhaven's success under the Council has become an impediment to the ambition of several rulers, and the mages protecting the town are seen as a threat. Taelya, a young and untried mage, finds herself at the heart of a conspiracy to destroy her home and the people she loves, and she may not be powerful enough to stop it in time"--